Formation of active-effective attitude of 12-13 years` judo athletes to sports functioning in competition period - Bliznevsky, A. A.; Kudryavtsev, M. D.; Iermakov, S. S.; Jagiello, W. (Archives of Budo, 2016)
Background and Study Aim: In competition functioning to aspects of attitude exist: orientation for achievement of success and orientation for avoiding of failure. The purpose of the research is theoretically and experimentally substantiate methodic of active-effective attitude to sports functioning formation in 12-13 years` judo athletes (youngster categories) in competition period.